Analisis Kemampuan Berfikir Komputasi Menggunakan Free Universal-Algebra Equation Solver - Nuria Ulfah Lubis; Yahfizham (INDO PUBLISHING, 2025)
This study aims to analyze students' computational thinking skills in solving algebra problems by utilizing the Free Universal-Algebra Equation Solver (FUAES) application. Computational thinking skills include several aspects, such as decomposition, abstraction, pattern recognition, and algorithm design, which are crucial skills in understanding and solving mathematical problems. By conducting a literature review, this study evaluates the extent to which FUAES is effective in helping students develop systematic and logical thinking patterns. The results of the study indicate that FUAES not only provides the final solution, but also presents the steps of the solution in a structured manner, thus contributing to improving students' computational thinking skills. However, the success of implementing this application is greatly influenced by students' learning motivation and the pedagogical approach applied by the teacher. These findings recommend the use of FUAES as an effective learning aid, if supported by reflective and participatory teaching strategies.